PAS-based isotopologic analysis of highly concentrated methane - Bahr, Marc-Simon; Wolff, Marcus (Frontiers in Environmental Chemistry, 2022)
Photoacoustic spectroscopy (PAS) is typically used for the detection of trace gases. In this way, mixtures of short-chain hydrocarbons such as methane, ethane or propane can be analyzed with detection limits in the range of parts per million (ppm) or parts per billion (ppb) or even below. However, there are a number of applications where highly concentrated mixtures need to be analyzed. In some cases even the isotopologic composition of certain hydrocarbons needs to be determined. Examples can be found in natural gas production and planetary research. We present PAS-based isotopologic analyses of two digit percentage-level methane concentrations in nitrogen. The investigation allows conclusions to be drawn about the extent to which PAS is suitable for an isotopologic analysis of undiluted natural gas-like mixtures.